2014
DOI: 10.2465/jmps.130624
|View full text |Cite
|
Sign up to set email alerts
|

Compositional zoning and inclusions of garnet in Sanbagawa metapelites from the Asemi-gawa route, central Shikoku, Japan

Abstract: Compositional and textural characteristics of the zonal structure and inclusions of garnet in metapelites from areas of high -grade greenschist facies (garnet zone) to areas of epidote -amphibolite facies (albite -biotite and oligoclase biotite zones) located along the Asemi -gawa route were examined using EPMA and Raman spectroscopy to investigate evolution of the P -T history of Sanbagawa metamorphism. Garnet grains exhibit two types of compositional zoning patterns: bell -shaped and composite types with spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Consequently, they assumed the ages of peak eclogites facies as~120-110 Ma by reference to the data of Okamoto et al (2004), though these age data were not obtained from the Asemi-gawa zircons, and interpreted that the young rim ages (88-81 Ma) represent zircon recrystallization during exhumation and retrograde stages. However, direct evidence for the eclogite facies equilibria are not confirmed from the basic and pelitic schists of the Asemi-gawa oligoclase-biotite zone, from which the sample studied by Aoki et al (2009) was collected (Taguchi and Enami, 2014a;Taguchi, T., personal communication, 2017). Additionally, zircon grains are a typical refractory phase, and thus it seems unlikely that recrystallization with decreasing temperature down to epidote-amphibolite facies conditions obliterated the ages for the eclogite facies stage of~120-110 Ma, as assumed by Aoki et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, they assumed the ages of peak eclogites facies as~120-110 Ma by reference to the data of Okamoto et al (2004), though these age data were not obtained from the Asemi-gawa zircons, and interpreted that the young rim ages (88-81 Ma) represent zircon recrystallization during exhumation and retrograde stages. However, direct evidence for the eclogite facies equilibria are not confirmed from the basic and pelitic schists of the Asemi-gawa oligoclase-biotite zone, from which the sample studied by Aoki et al (2009) was collected (Taguchi and Enami, 2014a;Taguchi, T., personal communication, 2017). Additionally, zircon grains are a typical refractory phase, and thus it seems unlikely that recrystallization with decreasing temperature down to epidote-amphibolite facies conditions obliterated the ages for the eclogite facies stage of~120-110 Ma, as assumed by Aoki et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Preserved paragonite and clinozoisite within garnet have also been reported in Sanbagawa schist in the Asemi-gawa area of central Shikoku (Taguchi and Enami, 2014). Therefore, prograde-zoned garnets can be potential rigid capsules retaining prograde mineral assemblages (Maruyama et al, 2010).…”
Section: Geological Significancementioning
confidence: 91%
“…They suggested that a part of the epidote-amphibolite facies zone (albite-biotite zone) has probably experienced the eclogite facies metamorphism, although no index phases of the eclogite facies equilibrium have been identified. In this study, coexistence of jadeite + quartz was newly discovered as an inclusion in garnet of a metapelite from the western extension of the southern albite-biotite zone along the Asemi-gawa route that was discussed by Taguchi and Enami (2014). This is direct evidence that at least part of the Asemi-gawa region has experienced high-pressure blueschist or eclogite facies metamorphism, and this finding prompted us to reevaluate the P-T path of the Sanbagawa metapelite in the Asemi-gawa region.…”
Section: Introductionmentioning
confidence: 92%
“…The Asemi-gawa region is divided into the chlorite, garnet, southern (lower) albite-biotite, oligoclase-biotite, and northern (upper) albite-biotite zones from south to north. Taguchi and Enami (2014) reported that composite-zoned garnet containing inclusions of paragonite and quartz with high residual retaining pressure characteristically occurs in the metapelite (sample AST72) from the southern albite-biotite zone (Fig. 1b), and they suggested the possibility that part of the schists of the Asemi-gawa region experienced the eclogite facies equilibrium.…”
Section: Geological Backgroundmentioning
confidence: 98%
See 1 more Smart Citation